2017
DOI: 10.1007/s10143-017-0842-z
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the surgical outcomes of tethered cord syndrome in adults: a retrospective study

Abstract: This study aimed to find the factors that may affect the surgical outcomes of congenital tethered cord syndrome (TCS) in adults by evaluating the long-term surgical outcomes of 25 consecutive cases. Medical records of 79 TCS cases which underwent surgery in Bakırköy Research and Training Hospital for Neurology, Neurosurgery and Psychiatry (BRSHH), during an 11-year period from 2005 to 2015, were retrospectively reviewed. All adult cases (patient age > 18 years) were selected as the core sample used for this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 21 publications
(36 reference statements)
0
21
0
Order By: Relevance
“…Our female patient had the same transit glob (retention of urination); however, she improved, as shown in Table 3 . Our review of the literature found that several studies suggested age, histology, previous surgery, tumor size, location, tumor consistency, and the extent of resection are not correlated with surgical morbidity, while removing 2 or more laminae can lead to spinal deformity, especially in children [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our female patient had the same transit glob (retention of urination); however, she improved, as shown in Table 3 . Our review of the literature found that several studies suggested age, histology, previous surgery, tumor size, location, tumor consistency, and the extent of resection are not correlated with surgical morbidity, while removing 2 or more laminae can lead to spinal deformity, especially in children [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…All the spinal ependymoma cases of children (patients age of under 18 years) are included in the current study (n=3). The patient characteristics, clinical presentation, surgical findings, and pre- and post-operative neurological functional assessments were evaluated using a modified neurological scoring system ( Table 1 ) [ 8 ], and long-term outcome are discussed. The relevant literature concerning ependymomas in children is also reviewed.…”
Section: Methodsmentioning
confidence: 99%
“…Compared to patients diagnosed at childhood, they exhibit more tolerance to certain symptoms. [ 24 ] When the spinal conus medullaris and nerve roots are affected, the patients suffer back pain, lower limbs weakness, foot deformities, spinal scoliosis, missing sensation, or bladder or rectum dysfunction. [ 22 , 23 , 25 27 ] The neurologic dysfunction occurring in adulthood is usually irreversible.…”
Section: Discussionmentioning
confidence: 99%
“…Patient characteristics, clinical presentation, surgical findings, pre-and postoperative neurological functional status, complications, and treatment outcomes were discussed. Pre-and postoperative neurological functional assessments had been evaluated using a modified neurological scoring system (Table 1) [9]. The neurological scoring system was introduced by Klekamp and Samii [10] in 1993 before being modified by Abdallah et al [9] in 2018 using urodynamic studies.…”
Section: Patient Data and Study Designmentioning
confidence: 99%
“…Pre-and postoperative neurological functional assessments had been evaluated using a modified neurological scoring system (Table 1) [9]. The neurological scoring system was introduced by Klekamp and Samii [10] in 1993 before being modified by Abdallah et al [9] in 2018 using urodynamic studies. The relevant literature concerning SSM in primary pediatric spinal MPEs was also briefly reviewed.…”
Section: Patient Data and Study Designmentioning
confidence: 99%